(untitled) (Bangladesh Rice Journal, 2023)
Bacterial blight disease (causal organism: Xanthomonas oryzae pv. oryzae) is an economically significant menace to rice cultivation in Bangladesh as well as in the world, which reduces significant yield loss in rice and hampers food security. The most sustainable strategy to fight this disease is the adoption of disease-resistant cultivars. The morphological trait and nature of diversity of 92 bacterial blight-resistant INGER (International Network for Genetic Evaluation of Rice) genotypes collected from the International Rice Research Institute (IRRI, Philippines) were analyzed to explore for sources of resistance. Artificial inoculation by BXO9, a virulent race of Xoo was used to evaluate and screen those genotypes in the field. Twelve genotypes, out of 92 had resistance, and another twelve had moderately resistance. Eleven morphological traits including disease data of each genotype were recorded and found noticeable diversity among the genotypes. Pearson’s correlation analysis among genotypes revealed that yield per hill is positively correlated with number of tiller per hill, number of effective tiller per hill, number of spikelets per panicle, number of filled spikelets per panicle and thousand grain weight. In cluster analysis, 15 major groups were obtained in ninety-two rice genotypes by using Euclidean distance and the UPGMA method. Cluster-1 comprises single genotypes SVIN310 which showed resistant reaction to bacterial blight disease had the highest tiller number, effective tiller number, number of spikelets per panicle, filled spikelets per panicle and thousand-grain weight. In PCA analysis, the first four principal components narrated around 77.32% variation. Among ninety-two genotypes, G1 (SVIN310), G23 (SVIN018), G70 (SVIN012), G75 (SVIN054), G33 (SVIN007), G48 (SVIN006), G80 (SVIN049), G90 (BRRI dhan84), G30 (SVIN290) near to the vector line of yield per hill are highly and positively responsive to the yield per hill. Considering all of these, cluster-1 having genotype SVIN310 with resistant phenomena would be the potential genotype for further use in a breeding program. Bangladesh Rice J. 26 (1): 17-31, 2022